2015
DOI: 10.1038/srep16438
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of electroencephalography and near-infrared spectroscopy during voluntary motor preparation

Abstract: We investigated the relationship between electrophysiological activity and haemodynamic response during motor preparation by simultaneous recording of electroencephalography (EEG) and near-infrared spectroscopy (NIRS). It is still unknown how exactly EEG signals correlate with the haemodynamic response, although the activation in the premotor area during motor preparation has been captured by EEG and haemodynamic approaches separately. We conducted EEG-NIRS simultaneous recordings over the sensorimotor area wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…Brain-imaging technologies fall into two broad categories: 1) structural imaging, such as computed tomography (CT) and 2) functional imaging, such as electroencephalography (EEG). Apart from invasive methods (e.g., electrocorticography), non-invasive functional imaging methods can be mainly categorized into 1) electrophysiological methods and 2) metabolic methods 4 . EEG is the most popular electrophysiological method widely used in many research areas such as neuroscience, neural rehabilitation, and brain-computer interface (BCI) 5–14 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Brain-imaging technologies fall into two broad categories: 1) structural imaging, such as computed tomography (CT) and 2) functional imaging, such as electroencephalography (EEG). Apart from invasive methods (e.g., electrocorticography), non-invasive functional imaging methods can be mainly categorized into 1) electrophysiological methods and 2) metabolic methods 4 . EEG is the most popular electrophysiological method widely used in many research areas such as neuroscience, neural rehabilitation, and brain-computer interface (BCI) 5–14 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Recently, simultaneous EEG and NIRS systems, so-called hybrid systems, have been gaining more attention 19–23 . NIRS is suitable for simultaneous and artifact-free recording with EEG because its near-infrared light does not interfere with the electrical EEG measurement 4 . Over the last decade, an increasing number of research approaches have focused on the use of simultaneously acquired EEG and NIRS.…”
Section: Background and Summarymentioning
confidence: 99%
“…The choice of the multimodal method of EEG-fNIRS simultaneous recording was aimed at exploring the electrophysiological and functional mechanisms underlying the voluntary activation of cortical areas involved in movement and pain processing one. The advantage of co-registration lies in being able to obtain functional and electrical data at low cost and with good tolerance to motor artifacts [19]. Moreover, the light emission in the near-infrared does not contaminate the electro-physiological signal [20] and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…For each participant, data were decomposed using the Infomax Independent Component Analysis Algorithm, with components representing noise artefacts (such as eye blinks or neck musculature) identified and removed before back-transforming the data into time-domain electrode signals 25,26 . As this study was interested in the scalp EEG signals originating from contralateral motor cortex, only data from a single electrode (scalp location - C3) commonly used to represent signals emanating from the motor cortex 2730 was analysed. Trials were identified from the timestamps of the joystick trigger press (target presentation), and movement initiation was detected when the Euclidian distance of the cursor extended beyond a predetermined ‘zero’ zone (5 pixels).…”
Section: Data Pre-processingmentioning
confidence: 99%